On the Nature of Public Interiority - Teston, Liz (UI Scholars Hub, 2020)
This essay explores the intersection between interiority, urbanism, and human perception. I view interiority as a condition of the senses rather than an indoor place. Revelations of interiority can be discovered within the urban realm, in public spaces, and in intimate interior conditions. I am especially interested in “public interiority” or these cases of interiority that can be found in exterior urban places. Understanding interiority as a perceived condition grounds the built environment in phenomenology, varied human experiences, and everyday conditions. Herein, I begin with an ontology of interiority, which focuses on various ways of perceiving the nature of things—phenomenology, structuralism, and object-oriented-ontology (OOO). From there, I will analyse a taxonomy of public interiorities, including various strains of form-based, programmatic, atmospheric, and psychological public interiorities. Using real-world examples from my previous research in Bucharest, Romania, New York, and Knoxville, Tennessee as well as well-established examples in art and design, I will then analyse various urban experiences of interiority, and the way built conditions shape experience. In this way, I will bring the interior to the city.